Willingness to accept COVID-19 vaccine among the elderly and the chronic disease population in China - Jiahao Wang; Beibei Yuan; Xinran Lu; Xiaoxue Liu; Li Li; Shufan Geng; Haijun Zhang; Xiaozhen Lai; Yun Lyu; Huangyufei Feng; Rize Jing; Jia Guo; et al. (Taylor & Francis Group, 2021)
A cross-sectional field survey was conducted from November 2020 to January 2021 among 7259 participants to investigate the public perception, willingness, and information sources for COVID-19 vaccination, with the focus on the elderly and non-communicable chronic disease (NCD) population. Multiple logistic regressions were performed to identify associated factors of the vaccination willingness. The willingness rate of the elderly to accept the future COVID-19 vaccine (79.08%) was lower than that of the adults aged 18-59 (84.75%). The multiple analysis didn't identify significant relationship between NCD status and the vaccination intention. The main reasons for vaccine hesitancy by the public were: concern for vaccine safety, low infection risk, waiting and seeing others getting vaccinated, concern of vaccine effectiveness and price. Their relative importance differed between adults aged 18-59 and the elderly, and between adults aged 18-59 with or without NCD. Perception for vaccination importance, vaccine confidence, and trust in health workers were significant predictors of the vaccination intention in both age groups. The elderly who perceived high infection risk or had trust in governments were more likely to accept the vaccine. Compared with the adults aged 18-59, the elderly used fewer sources for COVID-19 vaccination information and more trusted in traditional media and family, relatives, and friends for getting vaccination recommendations. To promote vaccine uptake, the vaccination campaigns require comprehensive interventions to improve vaccination attitude, vaccine accessibility and affordability, and tailor strategies to address specific concerns among different population groups and conducted via their trusted sources, especially for the elderly.